Improving Student Learning Outcomes with the Application of Differentiated Learning in PAI and BP Subjects at UPT SDN 09 Lunang - Nuri Novita Sari (BiCED Proceeding, 2024)
This study aims to improve student learning outcomes in class V through the application of Differentiated Learning using the Card Short method. The research was conducted in two cycles at UPT SDN 09 Lunang, focusing on developing students' abilities in learning according to their individual capabilities. The results showed that in Cycle I, only 50% of students achieved the Minimum Mastery Criteria (KKM), while in Cycle II, the number of students achieving KKM increased to 57.1%. Based on observations and reflections, improvements were implemented in each cycle to address obstacles in the learning process. The learning outcomes of students in Cycle II showed significant improvement. Therefore, it can be concluded that Differentiated Learning can improve student learning outcomes, although further cycles are needed to achieve more optimal results.